1996
DOI: 10.1021/ma951391i
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Ionically Conducting Alkoxy Ether/Alkoxy Mixed-Substituent Poly(organophosphazenes) and Their Use as Solid Solvents for Ionic Conduction

Abstract: A series of mixed-substituent poly(organophosphazenes) with the general structure {NP[OCH2CH2OCH2CH2OCH3] x [O(CH2) y CH3]2-x } n , where x = 1 and y = 2−9 was synthesized. These polymers are candidates for use as solid polymeric, ionic conduction media. The polymers were characterized by 1H, 13C, and 31P nuclear magnetic resonance spectroscopy, gel permeation chromatography, elemental microanalysis, infrared spectroscopy, and differential scanning calorimetry. The polymers were complexed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
66
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 20 publications
2
66
0
Order By: Relevance
“…Detailed characterizations were carried out by methods like infrared spectroscopy [29][30][31], nuclear magnetic resonance (NMR) [32][33][34][35][36][37][38][39][40] and viscosimetry [41][42][43][44] in order to clarify the interaction of the cations with a polymer network and their associated transport dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed characterizations were carried out by methods like infrared spectroscopy [29][30][31], nuclear magnetic resonance (NMR) [32][33][34][35][36][37][38][39][40] and viscosimetry [41][42][43][44] in order to clarify the interaction of the cations with a polymer network and their associated transport dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…However, PEOLiX complexes exhibit very low ambient conductivity, typically 10 −7 S/cm. Recently, several classes of polymer electrolytes based on comb polyphosphazene [17][18][19][20][21][22][23][24][25], polysiloxane [26][27][28][29][30][31][32][33][34][35] and borane containing polyethers [36] were found to exhibit higher ambient ionic conductivity. These results demonstrated that apWe dedicate this paper to Professor Dick Jones, polysilane pioneer and valued friend.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past three decades, ion-conducting polymers have been investigated as promising and safe alternatives to the commercially available electrolytes currently used in lithium batteries [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The initial discoveries that polymer complexes could be used as either liquid [1] or solid [2] ionic conductors has led to the development of a wide range of polymer-based electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…However, PEO is crystalline at room temperature and can be electrochemically unstable. Therefore, efforts have focused on the combination of PEO with amorphous polymers such as polyphosphazenes [3][4][5][6][7][8] and polysiloxanes [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] via copolymerization reactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation